Proceedings, high altitude revegetation workshop no. 11 - Keammerer, Warren R., editor; Hassell, Wendell G., editor; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1995)
The 11th high altitude revegetation workshop was held on March 16-18, 1994 at Colorado State University in Fort Collins, Colorado.
March 1995.
Keywords: Revegetation -- United States -- Congresses; Mountain plants -- United States -- Congresses; Tundra plants -- United States -- Congresses; Reclamation of land -- United States -- Congresses